Self-Body Image in Emerging Adulthood - Felisha Yap; Meiske Yunithree (Journal of Psychology and Social Sciences, 2025)
This study aims to examine differences in body image among emerging adults based on gender, age, and body mass index (BMI). Body image in this study consists of four dimensions: (1) self-perception of body shape, (2) Social comparison of body image, (3) Attentional focus on body image, and (4) Drastic shifts in body evaluations. A total of 389 emerging adults participated in the study. The Body Shape Questionnaire (BSQ) was used as the measurement instrument. Data were analyzed using the Mann–Whitney U test for gender and age differences, and the Kruskal–Walli’s test for BMI differences. The results show no significant differences in body image based on gender across the dimensions of self-perception of body shape (p = .219), comparing body image with others (p = .278), attitudes focused on body image (p = .363), and drastic changes in body perception (p = .138). Additionally, no significant differences were found across age groups in self-perception of body shape (p = .251), comparing body image with others (p = .092), attitudes focused on body image (p = .134), and drastic changes in body perception (p = .121). In contrast, a significant difference was found based on BMI (p < .001), indicating that BMI categories influence all four dimensions of body image. These findings suggest that body image among emerging adults is more strongly shaped by actual physical conditions such as BMI than by demographic factors. The results contribute to the development of psychological interventions aimed at addressing body image concerns in emerging adulthood.